Ojo blanco (obl) : un gene marcador del grupo de ligamiento iv en tribolium castaneum herbst (1988)
Some genetic aspects of a spontaneous mutation in T. castaneum, discovered in the Department of Biology of National University of Colombia (Bogota), were studied. The mutant gene christened "ojo blanco" (obl), is recessive autosomic, of excellent viability, complete penetrance and variable expression. The gene is phenotipically characterized by a depigmentation of the compound eyes and can be observed from the larval stage. Linkage tests with marker mutants for different groups were carried out. The marker "sooty", of the linkage group IV, gave positive results. The distance was estimated from 2843 descendants obtained from backcrosses in repulsion plase and 1630 in coupling phase. This distance was worked out as 15.64 ± 0.92 units between obl ands. It was not possible to determine if obl is on the left or the right hand side of s. Nor discrepancies between sexes, neither between phases were found in the recombination frequencies for the region between the two loci of chromosome IV.